HISTORICAL AND DEMOGRAPHIC CHARACTERISTICS OF KYRGYZ LIVING IN TAJIKISTAN (THE CASE OF THE PAMIR KYRGYZ) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the historical formation, demographic situation, and cultural characteristics of the Kyrgyz population living in Tajikistan. Particular attention is given to the Kyrgyz communities of the Pamir region, mainly residing in the Murghab district. The study analyzes historical migration processes, economic and cultural traditions, and the social structure of the Pamir Kyrgyz. The article also discusses the historical reasons for the settlement of Kyrgyz people in this region, socio-economic transformations during the Soviet period, and the impact of migration processes in the post-independence era. In addition, the role of language, traditions, and cultural values in preserving the ethnic identity of the Pamir Kyrgyz is highlighted. The study concludes that the Pamir Kyrgyz constitute an important historical and cultural part of the Kyrgyz diaspora in Central Asia
Keywords: Pamir Kyrgyz, Kyrgyz of Tajikistan, ethnography, migration, demography, nomadic culture, Central Asia, ethnic identity